ÓPERAS FILMADAS: ESTUDIO COMPARATIVO DE DON GIOVANNI DE JOSEPH LOSEY Y JUAN DE KASPER HOLTEN - Dra. Isabel VILLANUEVA BENITO (Fonseca, Journal of Communication, 2023)
From an artistic point of view, the adaptation of an opera to the cinema, traditionally has been considered a complex and controversial process. Don Giovanni, of W. A. Mozart, is one of the operas that has generated more audiovisual versions during the centuries XX and XXI, although very few films have finally been taken to the screen. This paper is focused on comparing the audiovisual versions Don Giovanni, by Joseph Losey (1979), and Juan by Kasper Holten (2010). Through a quantitative and qualitative methodology based on content analysis, this research reflects on the degree of intervention exercised by the language and audiovisual format used in the process of reinterpretation of the pre-existing operatic text.